1977
DOI: 10.1056/nejm197704282961704
|View full text |Cite
|
Sign up to set email alerts
|

Visual Lung-Sound Characterization by Time-Expanded Wave-Form Analysis

Abstract: To characterize lung sounds objectively, we examined, by means of time-amplitude plots, selected tape recordings of auscultatory phenomena considered by six observers to be typical of those in a standard classification. Normal lung sounds could not consistently be visually distinguished from adventitious sounds at conventional chart recorder speeds of 100 mm per second or less, but the differentiation was easily achieved when the time scale of the plots was raised to 800 mm per second. When discontinuous sound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
3

Year Published

1979
1979
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(95 citation statements)
references
References 7 publications
5
82
0
3
Order By: Relevance
“…Analysis of recordings from infants with classic wheeze indicated that the acoustic properties were very similar to those described in adults [10] whereas recordings from infants with ruttles confirmed the clinical impression that these are two distinctive respiratory sounds.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Analysis of recordings from infants with classic wheeze indicated that the acoustic properties were very similar to those described in adults [10] whereas recordings from infants with ruttles confirmed the clinical impression that these are two distinctive respiratory sounds.…”
Section: Discussionmentioning
confidence: 62%
“…These position statements define wheezes as high-pitched musical sounds and bronchi as low-pitched continuous sounds. The waveform pattern for classical wheeze has been described previously by MURPHY et al [10] as "continuous undulating sinusoidal deflections" replacing the normal waveforms of lung sounds. The wheeze is continuous, which means a duration of >250 ms [14].…”
Section: Discussionmentioning
confidence: 99%
“…In 1969, FORGACS [1] subjectively coined the term "white noise" (energy being evenly distributed over a wide range of frequencies) to describe normal breathing sounds recorded close to the subject's mouth or at the trachea. This is confirmed by the chaotic waveform revealed when the amplitude of these sounds is recorded in extended time mode [57]. In 1981, GAVRIELY et al [36] calculated mean spectral frequencies (inspiration and expiration phases) showing that the log amplitude response curve remained virtually flat from 75 Hz (high-pass filter cut-off point) to about 900 Hz, before rapidly falling away at higher frequencies.…”
Section: Bronchial Soundsmentioning
confidence: 89%
“…Crackles were defined in accordance with accepted criteria. 11,12 This lung-sound analyzer has been validated as a crackle counter. 6 Crackle pitch was measured from the crackle waveform, as the inverse duration (in seconds) of one complete sinusoidal cycle.…”
Section: Methodsmentioning
confidence: 99%